Humeral version in reverse shoulder arthroplasty affects impingement in activities of daily living - Kontaxis, Andreas; Chen, Xiang; Berhouet, Julien; Choi, Daniel; Wright, Timothy; Dines, David M.; Warren, Russell F.; Gulotta, Lawrence V. (Journal of shoulder and elbow surgery, 2017)
Impingement after reverse shoulder arthroplasty (RSA) has been correlated with implant design and surgical techniques. Previous studies suggested that humeral retroversion can reduce impingement and increase external rotation range of motion (ROM). The purpose of this study was to determine how humeral version affects impingement in activities of daily living (ADLs). A single surgeon performed virtual RSA on 30 arthritic shoulders that were reconstructed from preoperative computed tomography scans. For each subject, the humeral component was placed into 5 versions: −40°,−20°, 0°, +20°, and +40° (– indicates retroversion, + indicates anteversion). Intra-articular and extra-articular impingement was calculated for 10 ADLs. Impingement-free ROM was also calculated for abduction, forward flexion, scapula plane elevation, and internal/external rotation (standardized tests). Risk of impingement for ADLs was assessed as the collective duration and frequency of impingement across all motions. Frequent impingement sites were identified. For the ADLs, 0° version showed the least amount of impingement. In contrast, 40° retroversion resulted in the largest ROM for the standardized tests (118° ± 19° abduction, 109° ± 16° forward flexion, 111° ± 10° scapula plane elevation, 140° ± 15° internal/external rotation). The site of impingement changed with version: retroversion increased the extra-articular impingement, and anteversion increased the contact between the inferior glenoid and the humeral cup. Humeral version can significantly affect impingement in RSA. Maximizing ROM in standardized tests may not reduce the risk of impingement during ADLs. Our results showed that an average 0° of version should be preferred, but the large variability among subjects suggested that optimum version may vary among individuals.